Children's Speech Disorders Identification and Therapy Treatment - Karunasekara, Pasan; Deshitha, Sheshan; De Alwis, Dinuja; Karunarathna, Desan; Lokuliyana, Shashika; Gamage, Narmada (International Conference on Advancements in Computing (Online), 2023)
PhraseFluent is a project to develop a complete web-based solution to help people who are suffering from speech disorders. This application is specifically designed for people who are suffering from articulation and stuttering speech disorders. There are few solutions available for speech disorders identification and speech therapies. Those available applications have several drawbacks that lead to the research gap for this research. Those findings do not have any disorder-specific speech detection methods. Those applications generally detect speech disorders not the type of the disorder. Also, the speech therapy exercises suggest applications are practicing words according to the order of the alphabet. Those solutions are not based on the sounds that need to be practiced in order to cure speech disorders. Also, applications that have detection mechanisms are not currently available for wide access. This application mainly contains React-based interactive interfaces and a Python-programmed backend with machine-learning algorithms for functionality. This application can help to automate the process of detecting speech disorders and suggest therapy activities. Also, this application can track the patient's progress with the therapies. Used datasets contain the data with 70% accuracy and the test results gave a 68% percent success rate. This approach will be the first step in automating the complete process of speech disorder diagnosis.